Clients’ subjective experiences of navigating challenges in Gestalt therapy: an interpretative phenomenological analysis - Kaisler, Raphaela Elisabeth; Schaffler, Yvonne (Frontiers in Psychiatry, 2025)
IntroductionThis study explored the lived experiences of four female clients with common mental disorders and suboptimal structural integration after 30 sessions of Gestalt therapy, navigating emotional and relational challenges, bodily awareness, and agency.MethodUsing Interpretative Phenomenological Analysis (IPA), we analyzed four semi-structured interviews, followed by a cross-case comparison.ResultsTwo experiential patterns emerged. Clients with low-integrated personality structures faced significant difficulties with emotional regulation, self-concept stability, and relational dynamics. They relied heavily on external validation and struggled to develop cohesive internal processes. While they described increased awareness of emotions and bodily sensations, these experiences remained fragmented and did not translate into broader self-integration. In contrast, clients with moderate-integrated personality structures demonstrated greater emotional regulation and a more stable self-concept. However, despite engaging in reflective processing and linking past experiences to present challenges, they continued to struggle with self-agency.DiscussionFindings highlight the distinct ways in which clients with varying levels of personality integration experience Gestalt therapy and suggest that while emotional and relational growth occurred, deeper structural transformation remained limited. This study underscores the need for tailoring therapeutic interventions to clients’ structural integration levels, particularly by addressing the challenges of fostering agency in structurally vulnerable clients.